Distinct localization of GABAB receptors relative to synaptic sites in the rat cerebellum and ventrobasal thalamus - Kulik, Ákos; Nakadate, Kazuhiko; Nyíri, Gábor; Notomi, Takuya; Malitschek, Barbara; Bettler, Bernhard; Shigemoto, Ryuichi (European Journal of Neuroscience)
Metabotropic γ-aminobutyric acid receptors (GABABRs) are involved in modulation of synaptic transmission and activity of cerebellar and thalamic neurons. We used subtype-specific antibodies in pre- and postembedding immunohistochemistry combined with three-dimensional reconstruction of labelled profiles and quantification of immunoparticles to reveal the subcellular distribution of pre- and postsynaptic GABABR1a/b and GABABR2 in the rat cerebellum and ventrobasal thalamus. GABABR1a/b and R2 were extensively colocalized in most brain regions including the cerebellum and thalamus. In the cerebellum, immunoreactivity for both subtypes was prevalent in the molecular layer. The most intense immunoreactivity was found in Purkinje cell spines with a high density of immunoparticles at extrasynaptic sites peaking at around 240 nm from glutamatergic synapses between spines and parallel fibre varicosities. This is in contrast to dendrites at sites around GABAergic synapses where sparse and random distribution was found for both subtypes. In addition, more than one-tenth of the synaptic membrane specialization of spine-parallel fibre synapses were labelled at pre- or postsynaptic sites. Weak immunolabelling for both subtypes was also seen in parallel fibres but only rarely in GABAergic axons. In the ventrobasal thalamus, immunolabelling for both receptor subtypes was intense over the dendritic field of thalamocortical cells. Electron microscopy demonstrated an extrasynaptic localization of GABABR1a/b and R2 exclusively in postsynaptic elements. Quantitative analysis further revealed the density of GABABR1a/b around GABAergic synapses was higher than glutamatergic synapses on thalamocortical cell dendrites. The distinct localization of GABABRs relative to synaptic sites in the cerebellum and ventrobasal thalamus suggests that GABABRs differentially regulate activity of different neuronal populations.

Scaling limits of Schrödinger quantum mechanics - Erdös, László (Dynamics of Dissipation)
We outline the status of rigorous derivations of certain classical evolution equations as limits of Schrödinger dynamics. We explain two recent results jointly with H.T. Yau in more details. The first one is the derivation of the linear Boltzmann equation as the long time limit of the one-body Schrödinger equation with a random potential. The second one is the mean field limit of high density bosons with Coulomb interaction that leads to the nonlinear Hartree equation.

Two dimensional Pauli operator via scalar potential - László Erdös

Derivation of the Schrödinger-Poisson equation from the quantum N-body problem - Bardos, Claude; Erdös, László; Golse, François; Mauser, Norbert; Yau, Horng (Comptes Rendus Mathematique)
We derive the time-dependent Schrödinger–Poisson equation as the weak coupling limit of the N-body linear Schrödinger equation with Coulomb potential.

Linear Boltzmann equation as the long time dynamics of an electron weakly coupled to a phonon field - Erdös, László (Journal of Statistical Physics)
We consider the long time evolution of a quantum particle weakly interacting with a phonon field. We show that in the weak coupling limit the Wigner distribution of the electron density matrix converges to the solution of the linear Boltzmann equation globally in time. The collision kernel is identified as the sum of an emission and an absorption term that depend on the equilibrium distribution of the free phonon modes.

Pauli operator and Aharonov–Casher theorem¶ for measure valued magnetic fields - Erdös, László; Vougalter, Vitali (Communications in Mathematical Physics)
We define the two dimensional Pauli operator and identify its core for magnetic fields that are regular Borel measures. The magnetic field is generated by a scalar potential hence we bypass the usual A L 2loc condition on the vector potential, which does not allow to consider such singular fields. We extend the Aharonov-Casher theorem for magnetic fields that are measures with finite total variation and we present a counterexample in case of infinite total variation. One of the key technical tools is a weighted L 2 estimate on a singular integral operator.

Spectral shift and multiplicity of the first eigenvalue of the magnetic Schrödinger operator in two dimensions - Erdös, László (Annales de l'Institut Fourier)
We show that the lowest eigenvalue of the magnetic Schrödinger operator on a line bundle over a compact Riemann surface M is bounded by the L1-norm of the magnetic field B. This implies a similar bound on the multiplicity of the ground state. An example shows that this degeneracy can indeed be comparable with ∫M |B| even in case of the trivial bundle.

The Arabidopsis BODENLOS gene encodes an auxin response protein inhibiting MONOPTEROS-mediated embryo patterning - Hamann, Thorsten; Benková, Eva; Bäurle, Isabel; Kientz, Marika; Jürgens, Gerd (Genes and Development)
Developmental responses to the plant hormone auxin are thought to be mediated by interacting pairs from two protein families: short-lived inhibitory IAA proteins and ARF transcription factors binding to auxin-response elements. Monopteros mutants lacking activating ARF5 and the auxin-insensitive mutant bodenlos fail to initiate the root meristem during early embryogenesis. Here we show that the bodenlos phenotype results from an amino-acid exchange in the conserved degradation domain of IAA12. BODENLOS and MONOPTEROS interact in the yeast two-hybrid assay and the two genes are coexpressed in early embryogenesis, suggesting that BODENLOS inhibits MONOPTEROS action in root meristem initiation.

Multi-camera scene reconstruction via graph cuts - Kolmogorov, Vladimir; Zabih, Ramin (Proceedings of the 7th European Conference on Computer Vision)
In the last few years, several new algorithms based on graph cuts have been developed to solve energy minimization problems in computer vision. Each of these techniques constructs a graph such that the minimum cut on the graph also minimizes the energy. Yet because these graph constructions are complex and highly specific to a particular energy function, graph cuts have seen limited application to date. In this paper we characterize the energy functions that can be minimized by graph cuts. Our results are restricted to energy functions with binary variables. However, our work generalizes many previous constructions, and is easily applicable to vision problems that involve large numbers of labels, such as stereo, motion, image restoration and scene reconstruction. We present three main results: a necessary condition for any energy function that can be minimized by graph cuts; a sufficient condition for energy functions that can be written as a sum of functions of up to three variables at a time; and a general-purpose construction to minimize such an energy function. Researchers who are considering the use of graph cuts to optimize a particular energy function can use our results to determine if this is possible, and then follow our construction to create the appropriate graph.

Lateral relocation of auxin efflux regulator PIN3 mediates tropism in Arabidopsis - Friml, Jirí; Wiśniewska, Justyna; Benková, Eva; Mendgen, Kurt; Palme, Klaus (Nature)
Long-standing models propose that plant growth responses to light or gravity are mediated by asymmetric distribution of the phytohormone auxin. Physiological studies implicated a specific transport system that relocates auxin laterally, thereby effecting differential growth; however, neither the molecular components of this system nor the cellular mechanism of auxin redistribution on light or gravity perception have been identified. Here, we show that auxin accumulates asymmetrically during differential growth in an efflux-dependent manner. Mutations in the Arabidopsis gene PIN3, a regulator of auxin efflux, alter differential growth. PIN3 is expressed in gravity-sensing tissues, with PIN3 protein accumulating predominantly at the lateral cell surface. PIN3 localizes to the plasma membrane and to vesicles that cycle in an actin-dependent manner. In the root columella, PIN3 is positioned symmetrically at the plasma membrane but rapidly relocalizes laterally on gravity stimulation. Our data indicate that PIN3 is a component of the lateral auxin transport system regulating tropic growth. In addition, actin-dependent relocalization of PIN3 in response to gravity provides a mechanism for redirecting auxin flux to trigger asymmetric growth.

Hydra mutants of Arabidopsis are defective in sterol profiles and auxin and ethylene signaling - Souter, Martin; Topping, Jennifer; Pullen, Margaret; Friml, Jirí; Palme, Klaus; Hackett, Rachel; Grierson, Don; Lindsey, Keith (Plant Cell)
The hydra mutants of Arabidopsis are characterized by a pleiotropic phenotype that shows defective embryonic and seedling cell patterning, morphogenesis, and root growth. We demonstrate that the HYDRA1 gene encodes a Δ8-Δ7 sterol isomerase, whereas HYDRA2 encodes a sterol C14 reductase, previously identified as the FACKEL gene product. Seedlings mutant for each gene are similarly defective in the concentrations of the three major Arabidopsis sterols. Promoter::reporter gene analysis showed misexpression of the auxin-regulated DR5 and ACS1 promoters and of the epidermal cell file-specific GL2 promoter in the mutants. The mutants exhibit enhanced responses to auxin. The phenotypes can be rescued partially by inhibition of auxin and ethylene signaling but not by exogenous sterols or brassinosteroids. We propose a model in which correct sterol profiles are required for regulated auxin and ethylene signaling through effects on membrane function.

Cell polarity signaling in Arabidopsis involves a BFA sensitive auxin influx pathway - Grebe, Markus; Friml, Jirí; Swarup, Ranjan; Ljung, Karin; Sandberg, Göran; Terlou, Maarten; Palme, Klaus; Bennett, Malcolm; Scheres, Ben (Current Biology)
Coordination of cell and tissue polarity commonly involves directional signaling [1]. In the Arabidopsis root epidermis, cell polarity is revealed by basal, root tip-oriented, hair outgrowth from hair-forming cells (trichoblasts) [2]. The plant hormone auxin displays polar movements [1, 3] and accumulates at maximum concentration in the root tip [4, 5]. The application of polar auxin transport inhibitors [3] evokes changes in trichoblast polarity only at high concentrations and after long-term application [2, 4]. Thus, it remains open whether components of the auxin transport machinery mediate establishment of trichoblast polarity. Here we report that the presumptive auxin influx carrier AUX1 [6, 7] contributes to apical-basal hair cell polarity. AUX1 function is required for polarity changes induced by exogenous application of the auxin 2,4-D, a preferential influx carrier substrate. Similar to aux1 mutants, the vesicle trafficking inhibitor brefeldin A (BFA) interferes with polar hair initiation, and AUX1 function is required for BFA-mediated polarity changes. Consistently, BFA inhibits membrane trafficking of AUX1, trichoblast hyperpolarization induced by 2,4-D, and alters the distal auxin maximum. Our results identify AUX1 as one component of a novel BFA-sensitive auxin transport pathway polarizing cells toward a hormone maximum.

AtPIN4 mediates sink-driven auxin gradients and root patterning in Arabidopsis - Friml, Jirí; Benková, Eva; Blilou, Ikram; Wiśniewska, Justyna; Hamann, Thorsten; Ljung, Karin; Woody, Scott; Sandberg, Göran; Scheres, Ben; Jürgens, Gerd; Palme, Klaus (Cell)
In contrast to animals, little is known about pattern formation in plants. Physiological and genetic data suggest the involvement of the phytohormone auxin in this process. Here, we characterize a novel member of the PIN family of putative auxin efflux carriers, Arabidopsis PIN4, that is localized in developing and mature root meristems. Atpin4 mutants are defective in establishment and maintenance of endogenous auxin gradients, fail to canalize externally applied auxin, and display various patterning defects in both embryonic and seedling roots. We propose a role for AtPIN4 in generating a sink for auxin below the quiescent center of the root meristem that is essential for auxin distribution and patterning.

Polar auxin transport - Old questions and new concepts? - Friml, Jirí; Palme, Klaus (Plant Molecular Biology)
Polar auxin transport controls multiple aspects of plant development including differential growth, embryo and root patterning and vascular tissue differentiation. Identification of proteins involved in this process and availability of new tools enabling `visualization' of auxin and auxin routes in planta largely contributed to the significant progress that has recently been made. New data support classical concepts, but several recent findings are likely to challenge our view on the mechanism of auxin transport. The aim of this review is to provide a comprehensive overview of the polar auxin transport field. It starts with classical models resulting from physiological studies, describes the genetic contributions and discusses the molecular basis of auxin influx and efflux. Finally, selected questions are presented in the context of developmental biology, integrating available data from different fields.

A role for Neuregulin1 signaling in muscle spindle differentiation - Hippenmeyer, Simon; Shneider, Neil; Birchmeier, Carmen; Burden, Steven; Jessell, Thomas; Arber, Silvia (Neuron)
The maturation of synaptic structures depends on inductive interactions between axons and their prospective targets. One example of such an interaction is the influence of proprioceptive sensory axons on the differentiation of muscle spindles. We have monitored the expression of three transcription factors, Egr3, Pea3, and Erm, that delineate early muscle spindle development in an assay of muscle spindle-inducing signals. We provide genetic evidence that Neuregulin1 (Nrg1) is required for proprioceptive afferent-evoked induction of muscle spindle differentiation in the mouse. Ig-Nrg1 isoforms are preferentially expressed by proprioceptive sensory neurons and are sufficient to induce muscle spindle differentiation in vivo, whereas CRD-Nrg1 isoforms are broadly expressed in sensory and motor neurons but are not required for muscle spindle induction.

Observing structure, function and assembly of single proteins by AFM - Mueller, Daniel; Janovjak, Harald L; Lehto, Tiina; Kuerschner, Lars; Anderson, Kurt (Progress in Biophysics and Molecular Biology)
Single molecule experiments provide insight into the individuality of biological macromolecules, their unique function, reaction pathways, trajectories and molecular interactions. The exceptional signal-to-noise ratio of the atomic force microscope allows individual proteins to be imaged under physiologically relevant conditions at a lateral resolution of 0.5–1 nm and a vertical resolution of 0.1–0.2 nm. Recently, it has become possible to observe single molecule events using this technique. This capability is reviewed on various water-soluble and membrane proteins. Examples of the observation of function, variability, and assembly of single proteins are discussed. Statistical analysis is important to extend conclusions derived from single molecule experiments to protein species. Such approaches allow the classification of protein conformations and movements. Recent developments of probe microscopy techniques allow simultaneous measurement of multiple signals on individual macromolecules, and greatly extend the range of experiments possible for probing biological systems at the molecular level. Biologists exploring molecular mechanisms will benefit from a burgeoning of scanning probe microscopes and of their future combination with molecular biological experiments.

Processing of gene expression data generated by quantitative real-time RT-PCR - Müller, Patrick; Janovjak, Harald L; Miserez, Andre; Dobbie, Zuzana (Biotechniques)
Quantitative real-time PCR represents a highly sensitive and powerful technique for the quantitation of nucleic acids. It has a tremendous potential for the high-throughput analysis of gene expression in research and routine diagnostics. However, the major hurdle is not the practical performance of the experiments themselves but rather the efficient evaluation and the mathematical and statistical analysis of the enormous amount of data gained by this technology, as these functions are not included in the software provided by the manufacturers of the detection systems. In this work, we focus on the mathematical evaluation and analysis of the data generated by quantitative real-time PCR, the calculation of the final results, the propagation of experimental variation of the measured values to the final results, and the statistical analysis. We developed a Microsoft Excel-based software application coded in Visual Basic for Applications, called Q-Gene, which addresses these points. Q-Gene manages and expedites the planning, performance, and evaluation of quantitative real-time PCR experiments, as well as the mathematical and statistical analysis, storage, and graphical presentation of the data. The Q-Gene software application is a tool to cope with complex quantitative real-time PCR experiments at a high-throughput scale and considerably expedites and rationalizes the experimental setup, data analysis, and data management while ensuring highest reproducibility.

The percolation interpretation of the nuclear fragmentation phase transition - Bauer, Wolfgang; Bollenbach, Mark Tobias; Kleine Berkenbusch, Marko; Harreis, Holger (Proceedings of the 18th Winter Workshop on Nuclear Dynamics)

3d supernovae collapse calculations - Bollenbach, Mark Tobias; Bauer, Wolfgang
We give a brief overview of the current understanding of the explosion mechanism of core collapse supernovae. Our main focus is the impact of rotation on the explosion. Recent observations of the polarization of the light emitted by supernova explosions indicate that there are large deviations from spherical symmetry in the very heart of the explosion the origin of which is unknown. We use the new approach of a three dimensional test particle based simulation to simulate the infall phase of a supernova event. The underlying microphysics is simplified to make this computationally possible. A systematic study of the influence of rotation mainly during the infall phase of the collapse of a typical iron core is performed. Indications for significant deviations from spherical symmetry are found in our very rapidly rotating models. © 2002 American Institute of Physics

ICln Ion channel splice variants in Caenorhabditis elegans - Fürst, Johannes; Ritter, Markus; Rudzki, Jakob; Danzl, Johann G; Gschwentner, Martin; Scandella, Elke; Jakab, Martin; König, Matthias; Oehl, Bernhard; Lang, Florian; Deetjen, Peter; Paulmichl, Markus (Journal of Biological Chemistry)
ICln is an ion channel identified by expression cloning using a cDNA library from Madin-Darby canine kidney cells. In all organisms tested so far, only one transcript for the ICln protein could be identified. Here we show that two splice variants of the ICln ion channel can be found in Caenorhabditis elegans. Moreover, we show that these two splice variants of the ICln channel protein, which we termed IClnN1 and IClnN2, can be functionally reconstituted and tested in an artificial lipid bilayer. In these experiments, the IClnN1-induced currents showed no voltage-dependent inactivation, whereas the IClnN2-induced currents fully inactivated at positive potentials. The molecular entity responsible for the voltage-dependent inactivation of IClnN2 is a cluster of positively charged amino acids encoded by exon 2a, which is absent in IClnN1. Our experiments suggest a mechanism of channel inactivation that is similar to the “ball and chain” model proposed for the Shaker potassium channel,i.e. a cluster of positively charged amino acids hinders ion permeation through the channel by a molecular and voltage-dependent interaction at the inner vestibulum of the pore. This hypothesis is supported by the finding that synthetic peptides with the same amino acid sequence as the positive cluster can transform the IClnN1-induced current to the current observed after reconstitution of IClnN2. Furthermore, we show that the nematode ICln gene is embedded in an operon harboring two additional genes, which we termed Nx and Ny. Co-reconstitution of Nx and IClnN2 and functional analysis of the related currents revealed a functional interaction between the two proteins, as evidenced by the fact that the IClnN2-induced current in the presence of Nx was no longer voltage-sensitive. The experiments described indicate that the genome organization in nematodes allows an effective approach for the identification of functional partner proteins of ion channels.
Keywords: Cell Biology; Molecular Biology; Biochemistry